The irony in Antara's poetry, an analytical study (Journal of the College of Basic Education, 2022)
The term "irony" was not common in ancient Arabic monetary studies, such as its circulation or its prevalence in studies and research in our time, but it deals with names other than the term "irony", such as: exposure, praise, , Or metaphor, and so on, meaning that the name was present, but not under the name / term (paradox) that has been completed, and mature, almost in modern literature: poetry and prose, so that it became a new artistic phenomenon and modern technology is acquired by critics in the language of the new poem And the old, employed by the poet l Show the contradiction between two opposite sides. The technique of narrative paradox is one of the most important techniques used by poets in their hair, because it provides a great deal of poetry reduction, and condensation it contains, as well as provide a vision of the existence of a large dynamic and to raise the attention of the recipient. Hence, the term has been used in recent studies, and scholars have attached